Metaplastic breast carcinoma with osseous remnant post standard treatment of invasive ductal carcinoma: case report and review of literature - Keramati, Alireza; Shandiz, Fatemeh Homaei; Taghizadeh-Hesary, Farzad; Gharib, Masoumeh (European Journal of Oncology and Environmental Health, 2018)
Metaplastic breast carcinoma (MBC) is a rare subgroup of breast cancers that behave more aggressive in comparison with other breast cancer subtypes. Among them, the osseous variant is the rarest variant. Histologically, it consists of a metaplastic component beside main adenocarcinoma component. Consequently, this extra metaplastic part of MBC can justify more aggressive and chemoresistant behavior of metaplastic breast carcinoma. We present a case of a middle-aged female with metaplastic breast cancer that following standard chemotherapy of invasive ductal carcinoma, modified radical mastectomy with axillary lymph node dissection was performed. Surprisingly, related pathology report referred only to the mesenchymal component. The optimal treatment of MBC is not well-known yet, and the current approach is paralleled with other IDC subtypes. Therefore, studies about the MBC biologic markers can demonstrate new treatment approaches. This issue can be a milestone in the management of MBC, which targeting mesenchymal component in systemic therapy can improve clinical consequences.